FDI, technology & knowledge transfer from Nordic to Baltic countries - Arūnas Burinskas; Rasmus Bøgh Holmen; Manuela Tvaronavičienė; Agnė Šimelytė; Kristina Razminienė (Insights into Regional Development)
The purpose of this study is to examine the intensity of technology and knowledge transfer to the selected Baltic countries through foreign direct investment. The intensity of technology and knowledge transfer across the Baltic countries varies widely, with Estonia showing the leading position in the Baltic region. The amount of foreign direct investment in three countries is linked with the level of technology and knowledge transfer. It is indicated that during the Financial Crisis in 2008, the extent of foreign direct ownership changed in all three countries and later recovered. In the aftermath of this disruption, countries recovered their stock Foreign direct investment attraction rates and almost reached their 2004 level. Latvia has achieved a 50 per cent increase among Baltic countries, benefiting from it. Foreign direct investment and technology transfer increased through effective strategies and policies. In contrast, Estonia maintains a sustained stock foreign direct investment and has moderately lower margins than in other Baltic countries. Among countries, Estonia is the dominant stock FDI absorber in the Baltic region and have made significant contributions in the region.